A review on multiple criteria undesirable facility location problems - Tang, Sai Hong; Boyer, Omid; Pedram, Ali; Mohd Yusuff, Rosnah; Zulkifli, Norzima (TextRoad Publication, 2013)
This paper will review the research conducted on multi criteria location problem for undesirable facilities in two separate groups. First, multi attribute studies to select appropriate site for undesirable facilities such as landfill and treatment center are reviewed. Thereafter, some of the important and common criteria and sub-criteria to select site for landfill from reviewed studies are derived. Second, multi-objective model to locate undesirable facilities are surveyed. Also, different objectives that are considered usually in location undesirable facilities are extracted. This study can help decision makers and researchers to know significant criteria in field of undesirable facilities location problems. Also, it can help to have knowledge about solution methods to tackle multi criteria problem.